Chitosan-nanoparticle-based oral Salmonella enteritidis subunit vaccine elicits cross-protection against Salmonella typhimurium in broilers - Sara Dolatyabi; Sankar Renu; Jennifer Schrock; Gourapura J. Renukaradhya (Poultry Science, 2024)
ABSTRACT: Non-typhoidal Salmonella infection is a significant health and economic burden in poultry industry. Developing an oral vaccine to induce robust mucosal immunity in the intestines of birds, especially cross protection against different Salmonella serotypes is challenging. Therefore, a potent oral vaccine platform that can mitigate different serotypes of Salmonella is warranted for the poultry industry. We reported earlier that the Salmonella enteritidis (SE) immunogenic outer membrane proteins (OMPs) and flagellin (FLA) entrapped in mannose chitosan nanoparticles (OMPs-FLA-mCS NPs) administered prime-boost (d-3 and 3-wk later) by oral inoculation elicits mucosal immunity and reduces challenge SE colonization by over 1 log10 CFU in birds. In this study, we sought to evaluate whether the SE antigens containing OMPs-FLA-mCS NPs vaccine induces cross-protection against Salmonella typhimurium (ST) in broilers. Our data indicated that the OMPs-FLA-mCS NPs vaccine induced higher cross-protective antibody responses compared to commercial Poulvac ST vaccine (contains a modified-live ST bacterium). Particularly, OMPs-FLA-mCS-NP vaccine elicited OMPs and FLA antigens specific increased production of secretory IgA and IgY antibodies in samples collected at both post-vaccination and post-challenge timepoints compared to commercial vaccine group. Notably, the vaccine reduced the challenge ST bacterial load by 0.8 log10 CFU in the cecal content, which was comparable to the outcome of Poulvac ST vaccination. In conclusion, our data suggested that orally administered OMPs-FLA-mCS-NP SE vaccine elicited cross protective mucosal immune responses against ST colonization in broilers. Thus, this candidate vaccine could be a viable option replacing the existing both live and killed Salmonella vaccines for birds.